Influence of the acidity of electrolyzed water on the microhardness of inner layer dentin - Ker-Kong Chen; Ju-Hui Wu; Shin-I. Wei; Je-Kang Du (Elsevier, 2019)
Background/purpose: Electrolyzed water has been identified as an effective disinfectant that could represent as an alternative to sodium hypochlorite. Unfortunately, it remains unclear whether the texture or physical properties of dentin are affected by the application of electrolyzed water of different acidities. This study was aimed to assess the influence of electrolyzed waters with differing pHs on the demineralizing of inner dentin. Materials and methods: The coronal superficial dentin of 20 human molars was exposed and further bisected into two pieces perpendicular to the dentin surface. The samples were immersed in strongly acidic electrolyzed water (AW group), neutral electrolyzed water (NW group), 5% sodium hypochlorite (positive control, NL group), or deionized water (negative control, DW group). Microhardness of the inner layer dentin was measured at a depth of 25 and 50 μm beneath the superficial surface layer every 5 up to 60 min. Results: At a depth of 25 μm, microhardness decreased with increasing immersion time in all but the DW group. The AW group exhibited a decreasing trend from the first 5 min that became significant after 35 min of immersion and was the most rapid decrease in the four groups. The rate of decline in the NW group was low and similar to that of the NL group. Both NW and NL groups exhibited significantly less demineralization than the AW group after 15 min of immersion. No significant microhardness change was found at a depth of 50 μm in any of the samples. Conclusion: AW produces a more pronounced softening of dentin than NW at a depth of 25 μm. Keywords: Dentin, pH, Microhardness, Electrolyzed water, Tooth demineralization, Mouthwashes